Predictive value of platelet counts to detect grade of esophageal varices in liver cirrhosis - Sushma Swaraj Rapelly; Shalini Suri; Nabila Nishat; Afreen Saif (Journal of Family Medicine and Primary Care, 2025)
Introduction: Bleeding from esophageal varices (EVs) causes a significant risk in cirrhotic patients, often leading to life-threatening complications. While screening endoscopy is the recommended method to identify those at risk, its invasive nature and limitations prompt the search for alternative predictors. Thrombocytopenia has emerged as a potential marker for assessing the presence and severity of EVs. This study aims to establish a relationship between platelet count and predicted grading of EVs in individuals with liver cirrhosis. Aim: To study platelet count as a predictor of EVs in liver cirrhosis. Materials and Methods: This cross-sectional research was undertaken at KGMU, Lucknow. It encompassed newly identified cases of cirrhosis with varices of any degree detected through endoscopy. The endoscopic observations were standardized utilizing the Paquet grading system. Patients were categorized into four subgroups based on platelet count, and correlations between platelet count groups and EVs grading were examined using Spearman rank correlations. The association between platelet count and EVs grade was assessed using the Chi-square test. Results: The study comprised 50 patients, with 84% (n = 42) being male, and the mean age was 45.66 ± 10.26 years. Platelet counts were categorized as follows: <50,000/uL in 36% of patients, 50,000–99,000/uL in 28%, 100,000–150,000/uL in 14%, and >150,000/uL in 22% of patients. EVs were classified as grade I in 26% of patients, grade II in 20%, grade III in 34%, and grade IV in 20% of patients. When the platelet count is <50,000/uL, the patients present grade IV varices. With a platelet count of 50,000–99,000/μL, they present grade III varices; 100,000–150,000/μL corresponds to grade II; and > 150,000/μL to grade I EVs. The mean platelet count was 223245.53/mm3 in patients with grade I varices, decreasing to 109505.42/mm3, 57345.46/mm3, and 20502.00/mm3 in patients with grade II, III, and IV varices, respectively (p = <0.0001). A notable negative correlation was observed between platelet count and EVs grades (P < 0.001). Conclusion: Platelet count serves as a predictive factor for EVs grade in cirrhotic patients, with a significant negative correlation between platelet count and varices grades.